Perfil morfofisiológico do desenvolvimento e germinação de sementes e crescimento inicial de plântulas de Jatropha curcas L. - Brito, Cristiane Dantas de (2015)
The life cycle of a seed plant involves subsequent stages of development including seed formation, germination and seedling establishment. Together these stages represent the critical phase of intersection between two generations and are characterized by deep cytological, morphological, metabolic and physiological changes. Jatropha curcas L. (Euphorbiaceae) is popularly known as physic nut and produces seeds rich in oil with properties that allow its use in various industries, including the production of biodiesel. This study aimed to advance on the understanding of morphophysiological patterns and elucidate morphoanatomical adaptations involving embryogenesis, maturation, germination and seedling growth in J. curcas. Therefore, it was initially analysed and described the morphophysiological profile based on 13 stages of development and maturation associated to color of the fruit exocarp and seed coat, and description of the structures present at each stage (Chapter 1). Analysis of microtubular cytoskeleton configurations during embryogenesis showed cell cycle activity by the presence of cortical and mitotic microtubules during histodifferentiation and organogenesis, whilst it was possible to characterize a new organogenetic profile of embryogenesis revealed by the presence of a multimeristematic radicle and stomata in embryos of J. curcas seeds (Chapter 2). The multimeristematic embryos formed by a central apical meristem and four lateral meristems interconnected by a complex vascular system have revealed a new model of root formation during seed germination and seedling development, in which there is simultaneous protrusion of a larger main root and four smaller adventitious roots, all growing at the same time during the formation of the seedling root system (Chapter 3). The stomata occurred in the radicle-hypocotyl transition area, exhibited different sizes and ontogenic phases and short lifespan by degenerating during seedling development. This demonstrates it’s functioning as restricted to the simultaneous growth stage of the five roots during germination, apparently due to high demand in gas exchange and energy metabolism, and a likely evolution onto the lenticels present in the stem of this species (Chapter 4).